Peran Manajemen Kelas dalam Meningkatkan Budaya Islam di SMP Negeri 1 Parigi - Fitri Syifa Nuriah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
This study aims to discuss the role of classroom management in improving Islamic culture at SMP Negeri 1 Parigi. Using qualitative descriptive method. Data were collected through observation, interviews, and documentation. The findings show that classroom management significantly enhances Islamic culture in the school. The teachers implement strategies that are in line with Islamic values, such as role modeling and integrating worship practices into learning. This approach encourages positive religious attitudes among students, including increased participation in prayers and polite behavior. The involvement of teachers, students and parents further strengthens the implementation of Islamic culture, which extends beyond religious activities to daily interactions and the school environment. Ultimately, effective classroom management at SMPN 1 Parigi supports the achievement of academic goals and shapes students' characters according to Islamic values.